OpenFOAM computation of interacting wind turbine flows and control (I): free rotating case. Issue 1 (31st March 2021) - Chen, Goong; Gu, Cong; Hajaiej, Hichem; Morris, Philip J.; Paterson, Eric G.; Sergeev, Alexey
We develop high-fidelity blade resolved CFD for interacting turbine flows by the open source software OpenFOAM . Multi-turbine configurations are considered, aimed at a study of wind-turbine flows and their interactions. The preprocessing, coding, turbulence modelling and visualisation are discussed and described. An extension of our CFD work to a turbine operating in a two-phase flow is also included. Snapshots of interacting turbine flows are illustrated and dynamic motions can be viewed in animation videos. Two turbulence models, RANS k - ε and LES, were used.